Expression Study of LeGAPDH, LeACO1, LeACS1A, and LeACS2 in Tomato Fruit (Solanum lycopersicum) - Pijar Riza Anugerah; Fenny Dwivany; Rizkita Rahmi Esyanti (HAYATI Journal of Biosciences, 2015)
Tomato is a climacteric fruit, which is characterized by ripening-related increase of respiration and elevated ethylene synthesis. Ethylene is the key hormone in ripening process of climacteric fruits. The objective of this research is to study the expression of three ethylene synthesis genes: LeACO1, LeACS1A, LeACS2, and a housekeeping gene LeGAPDH in ripening tomato fruit. Specific primers have been designed to amplify complementary DNA fragment of LeGAPDH (143 bp), LeACO1 (240 bp), LeACS1A (169 bp), and LeACS2 (148 bp) using polymerase chain reaction. Nucleotide BLAST results of the complementary DNA fragments show high similarity with LeGAPDH (NM_001247874.1), LeACO1 (NM_001247095.1), LeACS1A(NM_001246993.1), LeACS2 (NM_001247249.1), respectively. Expression study showed that LeACO1, LeACS1A, LeACS2, and LeGAPDH genes were expressed in ripening tomato fruit. Isolation methods, reference sequences, and primers used in this study can be used in future experiments to study expression of genes responsible for ethylene synthesis using quantitative polymerase chain reaction and to design better strategy for controlling fruit ripening in agroindustry.